2002
DOI: 10.1063/1.1465117
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor nanostructures defined with self-organizing polymers

Abstract: We describe a technique to create very small semiconductor nanostructures, with sizes far beyond the limit of conventional optical lithography processes, by the use self-assembling diblock copolymers as nanolithographic masks. Quantum structures with very high aspect ratio of 1:10 were fabricated by dry etching. In a first step, so-called diblock copolymer micelles were generated in a toluene solution. These micelles were loaded by a noble-metal salt. After dipping a substrate into this solution, a monolayer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 16 publications
0
41
0
Order By: Relevance
“…The utilization of high-energy irradiation such as plasma, electron beam or ion-beam removes the block copolymer template and generates nanoparticle arrays in a single step. 436,437 The fabrication of Au, Pd and Pt nanoparticle arrays was successfully demonstrated by utilizing PS-b-PVP micellar template. 438,439 Spatz et al showed the tunable interspacing of Co and Co 3 O 4 nanoparticle arrays by employing PS-b-PVP copolymer with different block lengths.…”
Section: Block Copolymers In Thin Filmsmentioning
confidence: 99%
“…The utilization of high-energy irradiation such as plasma, electron beam or ion-beam removes the block copolymer template and generates nanoparticle arrays in a single step. 436,437 The fabrication of Au, Pd and Pt nanoparticle arrays was successfully demonstrated by utilizing PS-b-PVP micellar template. 438,439 Spatz et al showed the tunable interspacing of Co and Co 3 O 4 nanoparticle arrays by employing PS-b-PVP copolymer with different block lengths.…”
Section: Block Copolymers In Thin Filmsmentioning
confidence: 99%
“…Although these photovoltaic structures are Interestingly, some of these devices, when made in an inverted confi guration, can be made in the air to produce reasonable effi ciencies and, thus, may lead to more stable inorganic/polymer structures. 39,40 The combination of nanoparticles and inorganic nanostructures with polymers and organic molecules provides a solution -based tool kit for producing a wide range of new and novel electronic structures, such as the development of nanoparticle or organic -based displays using OLED -based technology. Recently ink -jet printing of such displays is becoming a viable alternative to conventional processing, which could have a real importance for white light displays for indoor lighting, where large area and low cost are critical.…”
Section: Organic -Inorganic Hybridsmentioning
confidence: 99%
“…[11,12] Remarkable progress in the preparation of highly ordered structures has been made by Möller and co-workers. [13][14][15] The authors have developed a method to prepare monofilms from gold-loaded diblock-copolymer micelles, which can be used as templates. The first steps of the preparation process involved the formation of micelles from AB diblock copolymers and the loading of the micellar core with metal salts in a suitable solvent.…”
Section: Introductionmentioning
confidence: 99%